Association of MAOA genetic variants and resilience with psychosocial stress: A longitudinal study of Syrian refugees - Clukay, Christopher J. (PLoS One, 2019)
Early childhood trauma can have profound and lifelong effects on adult mental health and psychosocial wellbeing. Nevertheless, responses to trauma are highly variable. Genetic variants may help explain variation in responses to trauma by identifying alleles that associate with changes in mental health measures. Protective factors, such as resilience, likely also play an important role in responses to trauma. The effects of genetic variants, in combination with protective factors, on psychosocial health are not well understood, particularly in non-Western contexts. In this study, we test the relative influence of genetic variants of monoamine oxidase A (MAOA, a gene proposed to influence the impact of childhood trauma on adult violence and antisocial behavior), levels of resilience, and exposure to traumatic events on psychosocial stress and mental health trajectories over time. We use data from a cohort of 12-18-year-old Syrian refugees who were forcibly displaced to neighboring Jordan (n = 399). DNA samples and survey data on trauma exposure, resilience (CYRM-12), and psychosocial stress were collected at three time points: baseline, ~13 weeks, and ~48 weeks. Using multilevel models, we identified an association of MAOA variant, in males only, with symptom scores of psychosocial stress on the Perceived Stress Scale (PSS) over time (p = 8.1 x 10(−4)). We also found that resilience is strongly associated with PSS (p = 7.9 x 10(−9)), underscoring the importance of protective factors in influencing levels of psychosocial stress. Furthermore, there was an additive effect wherein the sharpest reductions in perceived psychosocial stress are seen in low-activity MAOA males with low trauma exposure or high resilience levels. Our results highlight the value of studies that integrate genetic and psychosocial factors to better understand complex phenotypes, such as responses to trauma in contexts of high trauma exposure.